Chard (Beta vulgaris var. cicla) extract improved hyperglycemia-induced oxidative stress and surfactant-associated protein alterations in rat lungs. (November 2015) - Oztay, Fusun; Sacan, Ozlem; Kayalar, Ozgecan; Bolkent, Sehnaz; Ipci, Yesim; Kabasakal, Levent; Sener, Goksel; Yanardag, Refiye
Abstract Context: Chard is used as an antidiabetic agent by the diabetic patients in Turkey. Objective: The effect of chard extract [Beta vulgaris L. var. cicla (Chenopodiaceae)] on the antioxidant system and the expression of surfactant-associated proteins (SP) in the lungs of hyperglycemic rats were examined. Materials and methods: Hyperglycemia was induced by a single dose of streptozotocin (60 mg/kg) provided intraperitoneally. Fourteen days after the rats were rendered hyperglycemic, the chard (2 g/kg/d), insulin (6 U/kg/d), and chard plus insulin (as mentioned above) were administered to rats for 45 d. On day 60, rats' lungs were removed. Oxidative stress parameters and SP expression were assayed. Results: The lungs of hyperglycemic rats were characterized by the induced lipid and protein oxidation, elevated myeloperoxidase and xanthine oxidase activities, decreased glutathione levels, and reduced tissue factor and antioxidant enzymes activities (catalase, superoxide dismutase, glutathione peroxidase, and glutathione-S-transferase). Chard treatment alone and chard treatment combined with insulin were capable of achieving a regression of pulmonary oxidative stress, by inhibiting lipid and protein oxidation, and restoring the antioxidant system of hyperglycemic rats. SP-A expressions were significantly unchanged in all groups, whereas pro-SP-C and SP-D expressions were reduced in hyperglycemic rats. Pro-SP-C and SP-D levels were increased by chard and insulin administrations alone and combined in hyperglycemic rats. Discussion and conclusion: All treatments have a positive effect on the surfactant and antioxidant systems of the lungs of hyperglycemic rats. The best therapeutic effect was provided by treatment with chard extract alone in the compensation of hyperglycemic symptoms.